2016
DOI: 10.1007/s00701-016-2874-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery planning based on time-resolved CTA for arteriovenous malformation: a case report and review of the literature

Abstract: Stereotactic radiosurgery has long been recognized as the optimal form of management for high-grade arteriovenous malformations not amenable to surgical resection. Radiosurgical plans have generally relied upon the integration of stereotactic magnetic resonance angiography (MRA), standard contrast-enhanced magnetic resonance imaging (MRI), or computed tomography angiography (CTA) with biplane digital subtraction angiography (DSA). Current options are disadvantageous in that catheter-based biplane DSA is an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…developed permanent symptoms such as hemiparesis, reduced consciousness, visual, and ocular motor deficits. The median target volume in this study was larger than the aforementioned trials at 3.6 cm 3 (0.1-26.3 cm 3 ) with a median margin dose was 20 Gy (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The adverse event rates were found to be 3.2%, 5.8%, 6.7%, and 7.5% at 1, 2, 3, and 5 years, respectively.…”
Section: Avm Closure Ratesmentioning
confidence: 53%
See 1 more Smart Citation
“…developed permanent symptoms such as hemiparesis, reduced consciousness, visual, and ocular motor deficits. The median target volume in this study was larger than the aforementioned trials at 3.6 cm 3 (0.1-26.3 cm 3 ) with a median margin dose was 20 Gy (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The adverse event rates were found to be 3.2%, 5.8%, 6.7%, and 7.5% at 1, 2, 3, and 5 years, respectively.…”
Section: Avm Closure Ratesmentioning
confidence: 53%
“…Two separate studies by Willems et al and Essig et al have demonstrated that 4D-CTA can better delineate the AVM nidus when compared to traditional angiography (24,25). Additional studies have also demonstrated improved temporal resolution using 4D-CTA compared to angiography which can help distinguish the collateral and feeding vessels of the AVM (26)(27)(28). The benefits of the both these features in the radiosurgical planning is that it allows the physician to limit the treatment to the AVM nidus and spare the surrounding cerebral parenchyma decreasing the effects of radiation toxicity.…”
Section: Neurological Deficits and Toxicitymentioning
confidence: 99%
“…The results from Dashti et al [14] showed reduction or resolution of severe headaches and over a 70% reduction in T2 FLAIR in both the patients. Turner et al [2] reported full recovery from steroid-refractory RIN post-SRS for AVM, including complete resolution of severe headaches and hemiparesis with bevacizumab. Uysal et al [15] reported a patient with steroid-resistant RIN post-SRS for AVM who experienced improvement in headache, hemiparesis, and ambulation along with significant resolution of perilesional edema on computed tomography [15].…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS) is a proven treatment modality for inoperable high-risk arteriovenous malformations (AVM) [1]. However, SRS administration has been associated with late toxicities, such as radiation-induced necrosis (RIN), which can present symptomatically in 2–14% of patients and neuroradiologically in ≤46% [2]. Steroid therapy is the primary mean for managing RIN, while the efficacy of bevacizumab, an angiogenesis inhibitor, is currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the first series of AVM patients treated with GKRS using 4D dynamic volume CTA angiography for nidus localization and treatment targeting, either before or after the placement of the Leksell® Coordinate Frame G on the day of GKRS treatment. Previously, our institution has reported a single case in which the 4D-CTA was used as a DOS study for treatment planning, including the use of titanium frame pins, creating a significant image artifact [ 23 ]. This artifact has been well documented by other groups utilizing only CT-based treatment planning as an alternative to MRI [ 24 - 25 ].…”
Section: Discussionmentioning
confidence: 99%